Synthesis and antibacterial evaluation of novel 11-O-carbamoyl clarithromycin ketolides. Issue 16 (15th August 2017) - Jia, Li; Yan, Mi; Shen, Yan; Qin, Yinhui; Qiang, Shengsheng; Ma, Shutao
Graphical abstract: A series of novel 11-O-aralkylcarbamoyl-3-O-descladinosyl-3-oxo-clarithromycin derivatives were designed, synthesized and evaluated for their in vitro antibacterial activity. Some compounds exerted potent and broad-spectrum antibacterial activity. Highlights: 11-O-carbamoyl clarithromycin ketolides were designed and synthesized. These derivatives were evaluated for their in vitro antibacterial activity. They exhibited excellent activity against susceptible and resistant strains. Some compounds exerted potent and broad-spectrum antibacterial activity. Abstract: A series of novel 11-O-carbamoyl clarithromycin ketolides were designed, synthesized and evaluated for their in vitro antibacterial activity. The results showed that the majority of the target compounds displayed improved activity compared with references against erythromycin-resistant S. pneumoniae A22072 expressing the mef gene, S. pneumoniae B1 expressing the erm gene and S. pneumoniae AB11 expressing the mef and erm genes. In particular, compounds9, 18, 19 and22 showed the most potent activity against erythromycin-resistant S. pneumoniae A22072 with the MIC values of 0.5 μg/mL. Furthermore, compounds11, 18, 19, 24 and29 were also found to exhibit favorable antibacterial activity against erythromycin-susceptible S. pyogenes with the MIC values of 0.125–1 μg/mL, and moderate activity against erythromycin-susceptible S. aureus ATCC25923 and B. subtilis ATCC9372.